Prognostic value of cerebrospinal fluid free fatty acid levels in patients with acute ischemic stroke - Wei, Xue-Jun; Han, Meng; Wei, Guang-Chen; Duan, Chong-Hao (Frontiers in Human Neuroscience, 2015)
In this study, prognostic value of cerebrospinal fluid (CSF) Free fatty acid (FFA) levels in patients confirmed with acute ischemic stroke (AIS) was evaluated in a Chinese population. A prospective cohort designed study was conducted at our hospital of the Emergency department from November 2012 to September 2014. The National Institutes of Health Stroke Scale (NIHSS) score on admission was applied to assess CSF levels of FFA and specific severity degree of stroke. Evaluation of the prognostic outcomes of those stroke patients used the modified Rankin scale (mRS) scores at 90-day. Logistic regression analysis analyzed the prognostic value of FFA. NIHSS score results suggested a positive relationship between levels of CSF FFA levels and severity of stroke. There was an obviously higher trend of CSF FFA levels in patients with CE stroke than those of the non-CE stroke patients, with statistically difference (P<0.05). Further, CSF FFA levels were evidently lower in those 73 patients with favorable outcome when compared to those with unfavorable outcomes [0.21(IQR, 0.11-0.28) mmol/L VS. 0.36(IQR, 0.27-0.50) mmol/L, P<0.0001, P<0.0001]. Multivariate analysis results after possible confounders adjustment indicated that there was an increased risk of unfavorable outcome associated with CSF FFA levels ≥ 0.29 mmol/L (OR 5.12, 95%CI: 2.35–10.28; P<0.0001). Collectively, CSF level of FFA at admission was suggested to be a useful, independent short-term prognostic marker in Chinese patient with AIS.